2020
DOI: 10.1038/s41598-020-61566-2
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Outcomes in Patients Undergoing Paraesophageal Hiatal Hernia Repair

Abstract: Many patients with hiatal hernias (HH) are asymptomatic; however, symptoms may include heartburn, regurgitation, dysphagia, nausea, or vague epigastric pain depending on the hernia type and severity. the ideal technique and timing of repair remains controversial. this report describes short-term outcomes and readmissions of patients undergoing HH repair at our institution. All patients who underwent HH repair from January 2012 through April 2017 were reviewed. Patients undergoing concomitant bariatric surgery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
(29 reference statements)
0
12
0
Order By: Relevance
“…PEH, paraesophageal hernia; RAS, robotic assisted surgery; CLS, conventional laparoscopic surgery; SD, standard deviation, IQR, interquartile range. difference and even a possible increase in hospital stay in robotic PEH repair, but all these findings were statistically insignificant (2,(8)(9)(10).…”
Section: Length Of Staymentioning
confidence: 88%
See 3 more Smart Citations
“…PEH, paraesophageal hernia; RAS, robotic assisted surgery; CLS, conventional laparoscopic surgery; SD, standard deviation, IQR, interquartile range. difference and even a possible increase in hospital stay in robotic PEH repair, but all these findings were statistically insignificant (2,(8)(9)(10).…”
Section: Length Of Staymentioning
confidence: 88%
“…A retrospective study by Soliman et al, on 293 patients who underwent elective PEH repair found significant reductions in complication rates in the robotic surgery group (6.3 vs. 19.2%), whereas three other studies state no significant difference in postoperative complication rate (2,10,11). No statistical difference was found in reoperations, readmission rates and mortality between the modes of MIS (2,11,12).…”
Section: Perioperative Complications/mortalitymentioning
confidence: 94%
See 2 more Smart Citations
“…Laparoscopic anti-re ux surgery (LARS) is a widely-accepted treatment for gastroesophageal re ux disease (GERD), especially for those who have recurrent heartburn and regurgitation (1)(2)(3). Medicationrefractory GERD is often complicated by the presence of paraesophageal hernia (PEH) of varying severity; hernia repair is thus recommended as a supplementary treatment for fundoplication in LARS to reinforce treatment outcomes (1).…”
Section: Introductionmentioning
confidence: 99%